CONVERSATIONAL STRATEGIES IN MIXED GENDER CONVERSATION IN ENOLA HOLMES MOVIE - Dila, Arpa; Mustikawati, Yunitari; Fauzi, Rizki (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This thesis analyses the conversational strategies in mixed-gender conversation in the Enola Holmes movie. This movie is chosen because it offers a representation of complex conversations between characters of different genders. This research uses a qualitative approach with discourse analysis method to identify and analyze the conversational strategies used by the characters in various contexts in the film. Data were collected through transcription of the film's dialogues and analysis using a conversational theory framework. The results of the analysis show that in conversations between mixed genders, the characters in Enola Holmes use a variety of conversational strategies to achieve their communicative goals, including hedging strategies, tag questions, empty adjectives, and super polite forms as per Robin Lakoff's 1975 theory. The results of this research analysis show that women tend to use the tag questions communication strategy which was found 8 times, then hedging and empty adjectives which were both found 7 times and finally super polite form which was found 6 times. The findings provide insights into how interactions between mixed genders are represented in films and the contribution of films in shaping our understanding of gender conversations